Simulation and validation of spinal construct testing based on ASTM F1717 - Jeong, Byeong Cheol; Sim, On; Lee, Chiseung (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSpinal fixation constructs must demonstrate reliable mechanical performance before clinical use. ASTM F1717 provides a standardized vertebrectomy model for comparative static evaluation. This study assessed construct mechanics and examined whether validated finite element analysis (FEA) can support simulation based design decisions.MethodsConstructs comprised Ti-6Al-4V ELI pedicle screws and rods; the support blocks were UHMWPE. Testing followed ASTM F1717 under static compression and tension at 25 mm/min. Four screw configurations varied diameter and length (640, 650, 740, 750). A model form investigation compared a jig included model (JIM) and a jig excluded model (JEM) to quantify the tradeoff between accuracy and efficiency.ResultsExperiment–FEA agreement was strong across metrics, with errors in most cases below 5 percent; the largest deviation was 7.12 percent for the flexion force at 20 mm in the 740 group. Plastic deformation of the rod occurred before 20 mm, which supports using the reaction force at 20 mm as a robust comparator. Increasing screw diameter produced larger reaction forces than increasing screw length, while greater construct stiffness was associated with shorter yield displacement of the rod. Relative to JIM, JEM reduced computational time by about 20–32 percent while maintaining reaction force differences within about 0.3 percent in the verification runs.DiscussionValidated FEA reproduced ASTM F1717 construct behavior within prespecified acceptance bounds and can complement early design screening. The parametric analysis highlights diameter as the dominant geometric factor for construct level force response under the tested conditions, whereas length had a comparatively minor influence. These findings indicate that the evaluated screw configurations can enhance structural durability and surgical safety, and they support the use of validated FEA as a reliable alternative to selected physical tests during early stages of implant design.